2017
DOI: 10.3892/or.2017.5527
|View full text |Cite
|
Sign up to set email alerts
|

An ‘activatable’ aptamer-based fluorescence probe for the detection of HepG2 cells

Abstract: It is significant to develop a probe with sensitivity and specificity for the detection of cancer cells. The present study aimed to develop an ‘activatable’ aptamer-based fluorescence probe (AAFP) to detect cancer cells and frozen cancer tissue. This AAFP consisted of two fragments: aptamer TLS11a that targets HepG2 cells, and two short extending complementary DNA sequences with a 5′- and 3′-terminus that make the aptamer in hairpin structure a capable quencher to fluorophore. The ability of the AAFP to bind s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…By using HCC cell lines and frozen HCC tissue section, the probe emitted a strong fluorescent signal only in the presence of the target cancer cells. This versatile technology can be adapted for other aptamer sequences targeting various cancers and diseases [ 71 ].…”
Section: Development Of Aptamer Against Hccmentioning
confidence: 99%
“…By using HCC cell lines and frozen HCC tissue section, the probe emitted a strong fluorescent signal only in the presence of the target cancer cells. This versatile technology can be adapted for other aptamer sequences targeting various cancers and diseases [ 71 ].…”
Section: Development Of Aptamer Against Hccmentioning
confidence: 99%
“…Based on the special tertiary structures, aptamers have robust binding affinity and high specificity with targets, including small organic molecules, proteins, and even cells [ 18 20 ]. Moreover, aptamers also have the characteristics of being easily synthesized and modified so that they are widely used as cancer detection probes [ 21 ]. Functionalized nanomaterials based on aptamers for detection of cancer are also hotspots in recent years [ 22 , 23 ], such as quantum dots and silica nanoparticles [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, a great deal of researches reported that the strategy of graphene oxide-based fluorescent aptasensor for detection target is feasible [ 21 , 32 ]. Nevertheless, few studies have been carried out using a GO-based aptasensor for leukemia cells, so far.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, a short 5′ strand was added to the fluorescent tag FAM and a complimentary 3′ C-strand was conjugated to the fluorescent quencher Eclipse. The quencher prevented fluorophore expression unless the aptamer came into contact with its target, allowing a conformational change that separated the quencher from the fluorophore [ 93 ]. The activatable aptamer approach was taken further by Lei et al, who developed a theranostic method that not only activates a fluorescent signal upon interaction with its target, but induces the release of a drug.…”
Section: Recent Progress In Aptamer-based Biosensor Technologymentioning
confidence: 99%